Motion planning and simulation of a caterpillar robot - Seethapathy Janarthanan. (2008)
This report focuses on the computer aided dynamic simulation and motion planning of a caterpillar robot which was built by Assoc. Prof. Francis Malcolm Nickols at (NTU). This report also ascertains the dynamic capabilities of the robot by conducting motion analysis through computing motion equations.